2020
DOI: 10.1101/2020.04.18.20070904
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ongoing outbreak of COVID-19 in Iran: challenges and signs of concern with under-reporting of prevalence and deaths

Abstract: 1

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 47 publications
3
12
0
Order By: Relevance
“…The model successfully recreates the nationwide trend of the outbreak with one peak in deaths during late March and a second emerging peak that started back in late May due to relaxed NPI measures (see Figure 5b and 5c). Our model correctly forecasted the insurgence of the second epidemic peak [18]. Also, our estimates for point-prevalence and cumulative deaths are aligned with those we predicted based on air travel and excess mortality.…”
Section: Evaluating Effectiveness Of Intervention Measures and The Dysupporting
confidence: 76%
See 1 more Smart Citation
“…The model successfully recreates the nationwide trend of the outbreak with one peak in deaths during late March and a second emerging peak that started back in late May due to relaxed NPI measures (see Figure 5b and 5c). Our model correctly forecasted the insurgence of the second epidemic peak [18]. Also, our estimates for point-prevalence and cumulative deaths are aligned with those we predicted based on air travel and excess mortality.…”
Section: Evaluating Effectiveness Of Intervention Measures and The Dysupporting
confidence: 76%
“…By mid-March, WHO and the Chinese Government delivered several shipments of emergency medical supplies along with more than 200,000 additional test kits which helped with the diagnosis of more hospitalised patients [17]. Nevertheless, some of the preliminary analysis showed that Iran was only reporting less than 10% of its symptomatic cases during its first peak in late March [18,19]. From early April, as the country ramped up its testing capacity, MoHME started to report outpatients and carried out limited levels of contact tracing in several provinces (see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…We find that the corrected nationwide COVID-19-related deaths during each season is approximately 2.5 times higher than the number of confirmed deaths from MoHME and that both estimates follow a similar trajectory over time with particularly elevated levels of excess mortality during winter (i.e. approximately 2.8 times higher than the confirmed deaths at the time) which may indicate that a larger portion of deaths during the early stages of the epidemic were undercounted as also noted in our previous analysis [13].…”
Section: Estimating the Level Of Exposure Across The Populationsupporting
confidence: 77%
“…However, we find only 5 provinces with significantly higher levels of mortality in winter 1398 SH (22 December 2019 to 19 March 2020) (see Table 1). These provinces include Qom, Gilan (Guilan), Golestan, Mazandaran, and Qazvin which were reportedly hit the hardest by an early wave of the COVID-19 epidemic with a total of 3.48K (95%CI: 3.17K -3.78K) combined extra deaths [13]. This observation rejects any possible association between the excess mortality in fall and significant levels of undetected COVID-19-related deaths across the country.…”
Section: Did the Covid-19 Epidemic In Iran Start During Fall 2019?mentioning
confidence: 90%
See 1 more Smart Citation